Sistem Pengupahan Tenaga Kerja Ditinjau dari Prinsip Muamalah dan Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Edwin Hadiyan (JBIMA (Jurnal Bisnis dan Manajemen), 2015)
The problem of women labour in company are never stoped in public. That isues are interesting. The descrimination about women ever hold in the company. And that problem never finished. The discrimination and equality about women are showed very clear. The problem about harassment, is not stable, the discrimination ever act everywhere, some time there is not the stable about that problem. The gender inequality persists in companies, discrimination and marginalization of women are still on going on the world of work in Indonesia, where as the Act, Regulation, Instruction, ILO (International Labour Organization) set up everything so that it is clear there is no discrimination in a variety of factors. Why is this still going on, all those who care about the world of work have the courage to be and do their best to rectify the situation.